Electrochemically engineering defect-rich nickel-iron layered double hydroxides as a whole water splitting electrocatalyst. (3rd September 2019) - Shi, Bo; Han, Xinqi; He, Xingquan; Cui, Lili
Abstract: It is well proved that fabricating more defects on basal plane of layered double hydroxides (LDHs) is one of effective ways to boost the electrocatalytic performance for oxygen evolution reaction (OER). For the first time, the nickel iron LDHs (NiFe LDHs) with hierarchical morphology and abundant defects are simultaneously constructed by one-step electrodeposition (ED) strategy with easy operation, time-saving and green chemistry. Remarkably, the morphology is elaborately tailored by changing the species of doped anions which is unique. Also, the X-ray photoelectron spectroscopy (XPS) results elucidate that the Fe sites are in electron-rich state in LDHs which is revealed to enhance the catalytic activity strongly arising from the generation of oxygen vacancy. To deliver the current density of 10 mA cm −2, the optimal NiFe LDHs require the overpotential of 128, 106 mV for OER and hydrogen evolution reaction (HER), and achieve 100 mA cm −2 at the overpotential of 237, 242 mV, respectively. As a bifunctional electrocatalyst, the NiFe LDHs exhibit the current density of 10 mA cm −2 at a cell voltage of 1.55 V and 100 mA cm −2 at 1.76 V, which are lower than that of most of benchmarking materials reported previously. Graphical abstract: Image 1 Highlights: NiFe LDHs are synthesized through one-step electrodeposition method. The shapes of NiFe LDHs can be tailored by tuning different species of anion. NiFe LDHs display hierarchical morphology and numerous oxygen vacancies. NiFe LDHs present excellent OER and HER performance.